2019
DOI: 10.1177/1470593119870214
|View full text |Cite
|
Sign up to set email alerts
|

Seduced by “fakes”: Producing the excessive interplay of authentic/counterfeit from a Baudrillardian perspective

Abstract: Authenticity has often been considered to be a key theme in contemporary consumer culture. One of its manifestations is how branded market offerings can maintain authentic meanings, especially in a market increasingly saturated with counterfeit substitutes. By following a Baudrillardian perspective, we focus on fashion objects in the “branded luxury” category to problematize the sanctity of the authentic/counterfeit distinction. We argue that marketing literature generally attempts to normatively maintain and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 82 publications
0
23
0
3
Order By: Relevance
“…The rising visitor numbers to Christmas markets corroborate this point, highlighting that consumers are willing to suspend their disbelief so that they can continue to enjoy these Christmas-themed consumption experiences (Castéran and Roederer 2013). The acknowledgement of authenticity as a property deemed important, but whose absence can easily be rationalised, problematises its centrality in the production of market-mediated experiences (see also Hietanen et al 2020) (Figures 2 and 3).…”
Section: Christmas Marketspart Of the Christmas Traditions Portfoliomentioning
confidence: 67%
“…The rising visitor numbers to Christmas markets corroborate this point, highlighting that consumers are willing to suspend their disbelief so that they can continue to enjoy these Christmas-themed consumption experiences (Castéran and Roederer 2013). The acknowledgement of authenticity as a property deemed important, but whose absence can easily be rationalised, problematises its centrality in the production of market-mediated experiences (see also Hietanen et al 2020) (Figures 2 and 3).…”
Section: Christmas Marketspart Of the Christmas Traditions Portfoliomentioning
confidence: 67%
“…Beverland, 2005; Brunninge and Hartmann, 2019). However, it has also been suggested that in a consumer society of repetitious production of commodified offerings the meaning of anything “real” or “authentic” is increasingly problematic and elusive (Baudrillard, 2007; also Hartmann and Ostberg, 2013; Hietanen et al, 2020a). When consumers have “seen it all before” and nothing is any longer novel (Brown et al, 2003a), the past becomes abstracted, providing fertile grounds for managerial constructions of the most “authentic” look-alike versions of times past, foregone settings, and stories (Beverland, 2005; Brown et al, 2003a; Hamilton and Wagner, 2014).…”
Section: Nostalgic Consumption and The Rise Of Retromentioning
confidence: 99%
“…While modernity, in its attempt to rationalize and disenchant thought, has done much to ostracize the idea of an unspeakable and even directly unthinkable excess (Beyes and Steyaert, 2013; Pawlett, 1997; Roberts, 2013), we can find it in action everywhere in neurosis, perversion, and psychosis (e.g. Gabriel, 2012; Lambert, 2019; Schuster, 2016) and in the intensities of the “seductive” characteristics of consumption spectacles (Hietanen et al, 2020a). Derrida’s haunting denotes similar overwhelming relations but with a temporal twist that brings in “broken fragments of time” (Pors, 2016: 1646), where the historical force of hauntology exists, undergirding every present, and thus should be seen as in no way “an abnormal state” (Fiddler, 2019: 3).…”
Section: Enter the Specter In Contemporary Capitalist Societymentioning
confidence: 99%
“…Other studies on ethics and personal values proved useful. Although they relied on different theoretical perspectives, such investigations analyzed the relationship between materialistic values and ethics (Muncy & Eastman 1998;Manyiwa & Brennam 2016), Machiavellianism and moral identity (Chowdhury, 2020) "ethical products" consumption (Papaoikonomou 2013;Shaw & Newholm 2002) or consumption "ethically questionable" (Gudigantala & Bicen, 2019;Hietanen et al, 2019;Stringer, Mortimer & Payne, 2020).…”
Section: Articulations Between Ethics and Personal Valuesmentioning
confidence: 99%